Observing the Changes of Seed Germination during the Year - Bláha, Ladislav; Hermuth, Ji?í (Cutting-edge Research in Agricultural Sciences Vol. 3, 2020)
Germination usually shows a minimum in December, but mainly in January and in February. Maximum of germinability is observed in the spring and summer time. This phenomenon isn’t result of the dormancy or secondary dormancy because during of long term seed storage, germinability has similar curve every year, only number of germinative seeds stepwise decrease every year at every month of storage. Every species or cultivar of crops has a typical course of the germinability during the year. There are also species (crops), that have germination process during the year almost constant i.e., without variation during the year, but it is a minority of genotypes, rather exceptions. From the theoretical practical view, there is possibility (but not certainty!) that in case of testing the seed germination at begin or end of year at genotypes with large variability of germinability during the year, that this phenomenon have negative impact on seed certification by companies producing seeds for cultivation practice in some species.